Freshwater Sawfish Pristis microdon Latham, 1794 (Chondrichthyes : Pristidae) in the Kimberley region of Western Australia - Thorburn, Dean C.; Morgan, David L.; Rowland, Andrew J.; Gill, Howard S. (Zootaxa, 2007)
The Freshwater Sawfish Pristis microdon was captured in marine waters of King Sound, and estuarine and fresh waters of the Fitzroy and Robinson rivers, in the Kimberley region of Western Australia. In light of the IUCN listing of the species as critically endangered, non-destructive means, including tagging-recapture data and information from specimens found dead on the banks, were utilised. Observations of sexual maturity, annuli present on vertebrae, recaptures of tagged individuals and length-frequency data suggested that the freshwaters of the Fitzroy River are a nursery for this species where immature individuals (up to 2800 mm total length) remain for a maximum of four or five years. Morphology and counts of the number of rostral teeth indicated that, in most cases, the rostral tooth morphology can be used to differentiate male and female P. microdon and also are useful in distinguishing this species from the congeneric and sympatric Pristis clavata. Furthermore, differences in the relationship between rostrum length and total length between the sexes may provide an effective diagnostic tool for the collation of historical distribution and sex ratio data from rostrums held in private collections. Rostral tooth counts and length at age data also suggest that the synonymisation of P. microdon, Pristis zephyreus and Pristis perotteti is not warranted.